THE FIVE-YEAR ACCOUNTING PROGRAM–WITH DUE AND DELIBERATE SPEED. - Firmin, Peter A. (The Accounting Review, 1959)
The article focuses on the five-year accounting program, recommended by the American Institute of Certified Public Accountants. It recommended that the study of accounting be concentrated in a fifth year following a four-year undergraduate arts and sciences program. A fundamental assumption inherent in any five-year accounting program must be that the purpose of a university undergraduate program is to educate students rather than to train them. The implied objective of such a program is to place emphasis on stimulating and motivating the student to learn because education is of value per se rather than because it is a means to acquire a skill, which will provide a livelihood. The educational system in the U.S. utilizes the "course" as the mechanistic framework for imparting knowledge. Implementing the "education not training" objective requires that the content of a course be part of the fund of human knowledge, which should be acquired because of its intrinsic value. Furthermore, the ideas and concepts of such courses should be presented in an analytical and interpretive manner, which will stimulate logical and independent thought.